Pemidanaan Dibawah Pidana Minimum Bagi Anggota Polri Dalam Tindak Pidana Narkotika - Tetelepta, Brian; Wadjo, Hadibah Zachra; Latumaerissa, Denny (Faculty of Law Universitas Pattimura, 2025)
This study discusses narcotics crimes for members of the National Police Narcotics abuse can cause damage to the resilience of society, nation, and state. Parties who abuse narcotics according to Law Number 35 of 2009 consist of narcotics addicts regulated in Article 1 number 13 and abusers regulated in Article 1 number 15. Narcotics Addicts are people who use or abuse Narcotics and are in a state of dependence on Narcotics, both physically and psychologically, this study uses a normative Juridical research method, with the technique of collecting and analyzing legal materials is Literature Analysis. Perpetrators and victims of narcotics abuse come from all groups and ages, from children, adolescents, to adults. The spread of illegal drugs has spread and expanded all over the world. The sophistication and ease of transportation facilities and technology greatly facilitate the development of narcotics abuse. Increasingly sophisticated communication tools are one of the means that can facilitate the process of narcotics abuse because they can be done anywhere and anytime. This can be done quickly and easily, especially with the internet.